Determinant factors of early marriage in developing countries: a literature review - Dhonna Anggreni; Hari B. Notobroto; Oedojo Soedirham (AOSIS, 2023)
Introduction: Early marriage is carried out before the teenager is even 18 years old. It is estimated that around 650 million teenagers in the world are married before they are 18 years old. Early marriage does not only have an impact on adolescent health, but globally will also affect national security, social development, human rights, economic development, and gender equality. Objective: This literature review aims to examine the determinants of early marriage in developing countries. Materials and Methods: This study is a literature review using three databases, namely Science Direct, PubMed, and Wiley Online Library. The scientific literature used is scientific literature published between 2018 and 2022 and was selected based on predetermined inclusion and exclusion criteria. The number of articles analyzed was 13. Results: From the review conducted, it is known that the most common determinant factors for early marriage are educational factors, economic factors, and place of residence. However, other factors have an impact, such as ethnicity, religion, and exposure to the mass media. Conclusions: This review can be used by local policymakers as material for consideration in determining steps to prevent early marriage.